Music and the poetics of production in the Bolivian Andes. - Stobart, Henry (SOAS musicology series, 2006)
Music and the Poetics of Production in the Bolivian Andes is a musical ethnography of a Quechua-speaking community of northern Potosí, in the Bolivian Andes. Based on extensive fieldwork, it explores how music permeates the lives of this group of herders and agriculturalists, and how it is deeply interwoven with agricultural and social (re)production. In this harsh highland environment, persuading the earth to bear fruit is a perpetual challenge, and music emerges as an especially critical and dynamic medium; one that provides rich insights into broader social processes and values. Music and dance orchestrate the seasonal transformation of the landscape, coordinate processes of life and death, and articulate relations with outside social groups and the spirit realm.